Bridging citizen science and science communication: insights from a global study of science communicators - Roche, Joseph; Jensen, Eric A.; Jensen, Aaron M.; Bell, Laura; Hurley, Mairéad; Taylor, Aoife; Boissenin, Clara; Chase, Jon; Cherouvis, Stephanos; Dunne, Kali; Kashmina, Joanne; Massarani, Luisa; et al. (Frontiers in Environmental Science, 2023)
A large study of science communicators around the world was conducted as part of the GlobalSCAPE research project. All participants in the study indicated some level of science communication experience, with more than 11% choosing "citizen scientist" as one of their identities. This paper provides an overview of how science communication and citizen science are two independent fields of research and practice that have opportunities for overlap and mutually beneficial outcomes, particularly in terms of the practices of those working in areas of public engagement with science. In addition, qualitative results are presented regarding the experience of being a science communicator for those who identified as citizen scientists. The paper also showcases the first empirical insights from the GlobalSCAPE project, which exemplifies how multi-national research can be used to explore the challenges and opportunities faced by those individuals working in science communication and citizen science.